2018
DOI: 10.3390/nu10070844
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Serum Levels in Metabolic Syndrome Patients Treated with Three Different Diets: A Post-Hoc Analysis from a Randomized Controlled Clinical Trial

Abstract: Background: Irisin, a hormone-like myokine, regulates energy homeostasis and mediates the benefits of physical activity on health. Methods: To estimate the effect of different diets on irisin concentrations in subjects with the Metabolic Syndrome (MetS). Methods: Subjects with MetS were derived from a population survey; 163 subjects were enrolled and randomized to a: Low Glycaemic Index (LGID), Mediterranean (MD) or Low Glycaemic Index Mediterranean (LGIMD) Diet, and the groups were compared, also with 80 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
1
19
0
1
Order By: Relevance
“…The results showed greater expression of FNDC5 in the intervention group compared with that of the control group (Timmons et al, 2012 ). Although Osella et al ( 2018 ) examined the effects of different diets on the serum irisin-1 concentration and found that vegetable proteins and saturated fatty acids were positively associated with serum irisin-1. The authors did not examine the effects of exercise on serum irisin-1 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed greater expression of FNDC5 in the intervention group compared with that of the control group (Timmons et al, 2012 ). Although Osella et al ( 2018 ) examined the effects of different diets on the serum irisin-1 concentration and found that vegetable proteins and saturated fatty acids were positively associated with serum irisin-1. The authors did not examine the effects of exercise on serum irisin-1 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Since the change in caloric content and composition of the diet can significantly affect the change in body composition [ 47 ] and in the level of irisin [ 48 , 49 ], the volunteers were asked not to change their diet and to record the composition of the meals consumed on a daily basis. The portion size was determined based on a photo album of products and dishes [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…In experimental and human studies, adiponectin, visfatin, and omentin-1 had negative effects on bone, while leptin exerted positive actions (8)(9)(10). Additionally, the role of a specific adipo-myokine, irisin, has been recently described (11,12). It is thought that irisin plays a positive effect on hyperglycemia by stimulating glucose uptake in muscle cells (13).…”
Section: Hyperglycemia and Adipokinesmentioning
confidence: 99%
“…As far as bone metabolism, irisin may promote osteogenic differentiation, increase in cortical bone mass and strength, and reduction in the number of osteoclasts (14). Irisin resistance has been postulated in diabetes, with a consequent theoretical loss of all these positive effects on bone mass and strength (12,15).…”
Section: Hyperglycemia and Adipokinesmentioning
confidence: 99%